Structural basis of denuded glycan recognition by SPOR domains in bacterial cell division - Martín Alcorlo (Nature Portfolio, 2019)
SPOR domains are present in bacterial proteins that recognize cell-wall peptidoglycan strands stripped of the peptide stems. Here, Alcorlo et al. show that, indeed, the presence of peptide stems abrogates binding to a SPOR domain, and provide insights into the molecular basis for recognition.